The Influence Of Consumer Ethnocentrism, Social Media Usage, E-WOM, And Celebrity Worship On Purchase Intention: The Mediating Role Of Brand Association - Rosalia; Yulyanti Fahruna; Ana Fitriana; Barkah; Erna Listiana (Cattleya Darmaya Fortuna, 2025)
This research intends to examine how consumer ethnocentrism, social media usage (SMU), e-WOM, and celebrity worship affect consumers' intentions to buy Erigo local fashion products in Indonesia, using brand association as a mediator. Quantitative methods were used in this study, and using the approach of purposive sampling, involving 193 respondents. PLS-SEM was utilized for analyze data with aid of SmartPLS 4 software. The results indicate that consumer ethnocentrism, SMU, e-WOM, and celebrity worship positively and significantly affects the purchase intention, through brand association, both directly and indirectly. These results demonstrate that brand association is crucial in enhancing the correlation between these variables and purchase intention. The practical implication is that marketing strategies that encourage pride in local products through consumer ethnocentrism, effective use of social media, positive consumer reviews (e-WOM), and celebrity endorsements can enhance brand association and consumer purchase intentions toward local products like Erigo.